CONTRASTIVE ANALYSIS OF AL-IBĀRĀT AL-ISTILĀHIYYAH ARABIC–ENGLISH–FRENCH–INDONESIAN: A SEMANTIC STUDY - Shadiqul Wahdi; Uyun Thayyibah; Ira Ainul Latifah; Ahmad Dardiri; Wati Susiawati (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study originates from the issue of differences in idiomatic meanings across languages, which often create difficulties in understanding and translating non-literal expressions. Idioms in Arabic, English, French, and Indonesian are rooted in distinct cultural backgrounds and metaphorical frameworks; therefore, they require comparative analysis. This study aims to compare five Arabic idioms found in the book *Al-ʿIbārāt Al-Iṣṭilāḥiyyah fī Al-Lughah Al-ʿArabiyyah Al-Mu’āṣirah Tsalātsi Lughāt* by Mamdouh Khassara and colleagues, along with their semantic equivalents in English and French, as well as to identify their closest idiomatic equivalents in Indonesian. The research employs a qualitative descriptive method through a library-based study. Data were collected by examining all idiomatic entries in the book, identifying the forms and meanings of the Arabic–English–French idioms, and subsequently searching for the most equivalent idiomatic expressions in Indonesian. The findings reveal differences in metaphorical patterns: Arabic is predominantly characterized by cultural and grammatical metaphors, English and French tend to employ visual metaphors, while Indonesian mainly utilizes emotional and everyday-life metaphors. These findings affirm that idioms are strongly influenced by the culture of their speakers.